The social media value framework: development and validation of a conceptual framework for social media engagement and value creation - Littlewood, Kerry (Graduate School of Business (GSB), 2025)
As social media sites continue to dominate attention, consumers are overwhelmed with content, campaigns and information in today's virtual world. How do brands and marketers stand out and ensure that their social media communications result in value creation? Engagement and the intent to engage are fundamental when considering return on investment. Post COVID-19, there has been a shift in the use of digital platforms and time spent on social media platforms. While multiple studies have looked at behavioural and user acceptance theories to gauge social media use, this study looked to determine whether these factors are still relevant post COVID-19 as well as provide a holistic view across multiple behavioural theories. Further to this, the introduction of Artificial Intelligence (AI), which is changing the creation and consumption of content, brings a new complexity and requirement to further research on this topic. The aim of study was to investigate the various behavioural, emotive and social factors that may enhance or impede engagement on social media platforms, with the focus on the ultimate behaviour resulting in value creation for the organisation. The study examines how various usage theories influence intent to engage and whether these result in trust and loyalty. The study posits that perceived benefit and cost factors can be identified that statistically influence social media engagement with the resultant creation of value to consumers. The study was based on prior research results, which developed a social media framework through the lens of value-based performance measurement. This model was created to support organisations in understanding the value of social media and an approach to setting strategies and in turn measuring the impact of social media communications. Social media has changed the relationship between organisations and their customers and therefore the importance of understanding social behaviour of customers within the social media context has become extremely relevant. A large number of social media studies have looked at the socio-psychological behaviour of individual social media users using theories such as Social Cognitive Theory (Chiu et al, 2006 and Lin et al, 2009); Technology Adoption Model (Hossain & de Silva, 2009 and Kwon & Wen, 2010); Theory of Planned Behaviour (Casalo et al, 2015 and Chang & Zhu, 2011) and Social Influence Theory (Cheung & Lee, 2010 and Koo et al, 2011). While the Social Media Value Chain (SMVC), derived from previous research by Littlewood and Bick (2015), considers the complexity of consumers and influencers, the framework needed to be further developed to incorporate these behavioural factors for organisations to fully understand how social media communications are engaged with and ultimately the value creation for both the consumer and the firm. Using the lens of Social Exchange Theory (SET), this study looked to a multidimensional model incorporating factors from the Theory of Reasoned Action (TRA), the Technology Acceptance Model (TAM) and the Theory of Planned Behaviour (TPB) to create a framework to understand consumer engagement with social media communications and the resulting value creation for organisations. Using factors identified in the Social Media Value Chain (SMVC) together with behavioural and usage theories, the research incorporated the antecedents and moderators of social media engagement and validated this through a confirmatory quantitative survey. The output was a conceptual framework that will assist organisations in understanding the determinants of consumer engagement and what needs to be considered for social media strategy creation and measurement. This study used a deductive quantitative method. Data was obtained using an online survey with closed-ended questions for demographic responses and a seven-point Likert scale as the measurement scale for the identified constructs. A total of 493 surveys were collected with 411 usable surveys from a global audience. Various statistical techniques were used for the analysis, including confirmatory factor analysis and structural equation modelling. The findings of the study reveal that two of the benefit factors have influence on the intent to engage and be satisfied with brands' social media platforms: Perceived usefulness had the highest overall influence on this intention, followed by perceived enjoyment, suggesting a shift aware from pure enjoyment post COVID-19. Five benefit and cost factors, including perceived usefulness, perceived enjoyment, reciprocal communication, privacy concern and social media fatigue had a significant influence on trust and loyalty. Interestingly, perceived usefulness again showed the highest influence, however this was a negative influence suggesting factors such as misinformation and disinformation are impacting online experiences. Social media fatigue also saw an opposite influence with a positive relationship to trust and loyalty; however, this follows the paradoxical behaviour and suggests that consumers could be increasing their trust and loyalty to specific brands due to the overwhelming amount of content and choices on social media. The strongest relationship was the engagement intention on trust and loyalty, supporting literature's findings around the influence of satisfaction on both trust and loyalty and increasing consumer demands. This study brings together multiple behavioural, social and usage models and extends the current knowledge on social media engagement and value creation, with a focus on exchange theory and benefits versus costs. The study's findings will assist marketers and industry specialists to better understand the impact of behaviour post the pandemic and how to adapt effective engagement strategies to drive trust and loyalty. Additional insight around negative factors, including social media fatigue, highlight the paradoxical behaviour seen on social media platforms. Further to this, the discussion and recommendations explores brands' responsibility when it comes to the social media perceived costs such as social media fatigue, privacy, as well as additional negative impacts of social media including disinformation and what a brand's role is in this space to protect mental health and wellbeing.